Stereotypes in Rebecca Hall™s Movie Passing - Bnagun, Misa Apulina; Bahri, Syamsul (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
The objectives of this study were 1) to investigate the pattern of stereotype analysis appeared in Passing movie, 2) to describe characters response the stereotypes that is aimed at them in the movie Passing, 3) to explain the reason characters in Passing movie confront stereotypes instead of conforming. The data in this study are taken from sentences in dialog and scripts contained in the film Passing. 1) There were three types of stereotype patterns according to Brand and Reyna's (2011) theory depicted in the movie Passing. The three types are: Internal/controllable/stable (63.20%) followed by, Internal/uncontrollable/stable (25.50%), and External/uncontrollable/stable (11.3%). 2) The types of resistance reflected in the movie Passing based on King's (2010) theory are Acquiescence (35.71%) followed by Violence (35.71%), and Non-Violence (28.57%). 3) There were three reasons why Black individuals accept stereotypes instead of conforming, based on King's (2010) theory. The first reason is the fear of retaliation, which can lead to conflict. The second reason is a lack of educational awareness, which suggests that white individuals tend to have a broader perspective compared to black people. The third reason is the lack of resources in terms of legal support and financial stability.